Clinical Practice Guideline for the Management of Antithrombotic Agents in Patients Undergoing Gastrointestinal Endoscopy - Hyun Lim; Eun Jeong Gong; Byung-Hoon Min; Seung Joo Kang; Cheol Min Shin; Jeong-Sik Byeon; Miyoung Choi; Chan Guk Park; Joo Young Cho; Soo Teik Lee; Ho Gak Kim; Hoon Jai Chun (Korean Society of Gastrointestinal Endoscopy, 2020)
Antithrombotic agents, including antiplatelet agents and anticoagulants, are increasingly used in South Korea. The management of patients using antithrombotic agents and requiring gastrointestinal endoscopy is an important clinical challenge. Although clinical practice guidelines (CPGs) for the management of patients receiving antithrombotic agents and undergoing gastrointestinal endoscopy have been developed in the Unites States, Europe, and Asia Pacific region, it is uncertain whether these guidelines can be adopted in South Korea. After reviewing current CPGs, we identified unmet needs and recognized significant discrepancies in the clinical practice among regions. This is the first CPG in Korea providing information that may assist endoscopists in the management of patients on antithrombotic agents who require diagnostic or elective therapeutic endoscopy. This guideline was developed through the adaptation process as an evidence-based method, with four guidelines retrieved by systematic review. Eligible guidelines were evaluated according to the Appraisal of Guidelines for Research and Evaluation II process, and 13 statements were established using a grading system. This guideline was reviewed by external experts before an official. It will be revised as necessary to cover changes in technology, evidence, or other aspects of clinical practice.